Categorization and delineation of agricultural prime and marginal lands of Nagpur district, Maharashtra for different uses - THELKAR, SONAL I.; SRIVASTAVA, RAJEEV; PATIL, N. G.; PRASAD, JAGDISH; NAGARAJU, M. S.S.; CHATTARAJ, S. ,; REDDY, G.P. OBI; NASRE, R. A.; WAKODE, ROSHAN R. (Journal of Soil and Water Conservation, 2017)
The present investigation was undertaken to delineate agricultural prime, moderate prime and marginal lands in Nagpur district Maharashtra based on land use, slope and soil characteristics. The extent of prime lands in the district is about 470418.30 ha (47.5% of TGA) to which Kuhi, Mauda, Saoner and Bhiwapur tehsils contribute, 61378.70 ha, 57051.69 ha, 41038.90 ha, and 41020.58 ha, respectively. The extent of moderate prime lands is about 85096.00 ha (8.60% of TGA), which may be utilized through adoption of appropriate agro-management. Out of 74699.73 ha (7.55 % of TGA) marginal lands, Katol contributes large area (23205.20 ha) followed by Kalmeshwar (8337.75 ha), Hingna (8240.43 ha) and Narkhed (8151.97 ha) tehsils. The study also indicate that prime agricultural lands are mostly located around the 4th and 5th stream orders and hence, stream order may be used as an indicator for identification and delineation of prime agriculture lands. The delineation of prime lands will be helpful in land use planning, protection of prime lands and sustainable utilization of lands. The quantification will help in prioritizing the area and judging the magnitude of efforts required to overcome the constraints.